AIM2/IL-1α/TGF-β Axis in PBMCs From Exacerbated Chronic Obstructive Pulmonary Disease (COPD) Patients Is Not Related to COX-2-Dependent Inflammatory Pathway - Molino, Antonio; Terlizzi, Michela; Colarusso, Chiara; Rossi, Antonietta; Somma, Pasquale; Saglia, Alessandro; Pinto, Aldo; Sorrentino, Rosalinda (Frontiers in Physiology, 2019)
Chronic obstructive pulmonary disease (COPD) is a lung disorder characterized by persistent respiratory symptoms and progressive airflow limitation as a consequence of chronic inflammatory response. Corticosteroids are the main treatment for COPD patients with a history of exacerbation, in that they attenuate exacerbation and dyspnea, and improve the response to bronchodilators. Nevertheless, although corticosteroids administration, COPD patients still undergo exacerbation phases. In this context, the aim of this study was to evaluate the activity of Absent in melanoma 2 (AIM2) inflammasome-dependent pathways under corticosteroids treatment during COPD exacerbation. Stable and exacerbated COPD-derived Peripheral Blood Mononuclear Cells (PBMCs) were treated with a well-known anti-inflammatory agent, Dexamethasone (DEX), in the presence or not of Poly (deoxyadenylic-deoxythymidylic) acid (Poly dA:dT), an AIM2 ligand. We found that IL-1α was highly increased when AIM2 was activated from Poly dA:dT in exacerbated, but not in stable, COPD-derived PBMCs. To note, the release of IL-1α after the stimulation of AIM2 in PBMCs obtained from stable (hospitalized) COPD patients was not higher from the basal conditions, though it was still as high as that observed for Poly dA:dT-stimulated PBMCs obtained from exacerbated patients. This effect was associated to higher expression of AIM2 in pair-matched circulating CD14+ cells obtained from hospitalized patients who passed from the exacerbation to the stable status. Because the difference between stable and exacerbated COPD patients stands on the treatment with corticosteroids, exacerbated and stable COPD-derived PBMCs were treated with DEX. Indeed, the release of IL-1α and TGF-β were not altered after DEX treatment. In conclusion, we found that the administration of DEX in vitro on exacerbated COPD-derived PBMCs was not able to revert the detrimental inflammatory mechanism associated to AIM2 activation responsible for the release of IL-1α and the ensuing TGF-β, contributing to the severity of disease.